2010
DOI: 10.1099/ijs.0.008292-0
|View full text |Cite
|
Sign up to set email alerts
|

Mangrovibacter plantisponsor gen. nov., sp. nov., a nitrogen-fixing bacterium isolated from a mangrove-associated wild rice (Porteresia coarctata Tateoka)

Abstract: Mangrovibacter plantisponsor gen. nov., sp. nov., a nitrogen-fixing bacterium isolated from a mangrove-associated wild rice (Porteresia coarctata Tateoka A facultatively anaerobic, nitrogen-fixing bacterium, strain MSSRF40 T , was isolated from roots of mangrove-associated wild rice (Porteresia coarctata Tateoka). On the basis of 16S rRNA gene sequence similarities, strain MSSRF40 T was shown to belong to the family Enterobacteriaceae, most closely related to Cronobacter muytjensii E603 T (97.2 % sequence simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
4
31
0
Order By: Relevance
“…The component C 17 : 0 was found in three members of the genus Yersinia tested in this study and has been reported for the genus Yersinia and other genera within the family Enterobacteriaceae by other authors (Jantzen & Lassen, 1980;Kämpfer et al, 2005;Whittaker et al, 2005;Madhaiyan et al, 2010;Rameshkumar et al, 2010).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The component C 17 : 0 was found in three members of the genus Yersinia tested in this study and has been reported for the genus Yersinia and other genera within the family Enterobacteriaceae by other authors (Jantzen & Lassen, 1980;Kämpfer et al, 2005;Whittaker et al, 2005;Madhaiyan et al, 2010;Rameshkumar et al, 2010).…”
supporting
confidence: 89%
“…The amplification, sequencing and phylogenetic analysis of the three genes were carried out as described previously (Rameshkumar et al, 2010 T in the genus Budvicia. These data revealed that rpoB, gyrB and hsp60 sequences have a high phylogenetic resolution for species identification in the family Enterobacteriaceae.…”
mentioning
confidence: 99%
“…For example, the type strain of Mangrovibacter plantisponsor (Rameshkumar et al, 2010) shares 97.2 % 16S rRNA gene sequence similarity with Cronobacter muytjensii E603 T and 97.1 % similarity with Enterobacter cloacae subsp. dissolvens LMG 2683…”
Section: Pseudomonas Flectens Atcc 12775mentioning
confidence: 99%
“…Grows on MacConkey agar. The following results are obtained from API 20E strips after 48 h of incubation at 28 u C: Larabinose fermentation is variable (negative for the type strain), D-mannitol, inositol, sorbitol, rhamnose and amygdalin are not fermented; acetoin is produced Brady et al, 2010;Brenner & Farmer, 2005;Hollis et al, 1981); 3, Pantoea (Pantoea agglomerans DSM 3493 T : Brenner & Farmer, 2005;Gavini et al, 1989;Kageyama et al, 1992;Mergaert et al, 1993); 4, Leclercia (Leclercia adecarboxylata DSM 30081 T : Brenner & Farmer, 2005;Rameshkumar et al, 2010;Tamura et al, 1986); 5, Raoultella (Raoultella planticola DSM 3096 T : Brenner & Farmer, 2005;Drancourt et al, 2001;Gavini et al, 1986) Brenner & Farmer, 2005;Grimont & Grimont, 2006;Rameshkumar et al, 2010); 10, Cedecea (Cedecea davisae DSM 4568…”
Section: Description Of Phaseolibacter Gen Novmentioning
confidence: 99%
“…For example, the type strain of Mangrovibacter plantisponsor (Rameshkumar et al, 2010) shares 97.2 % 16S rRNA gene sequence similarity with Cronobacter muytjensii E603 T . Moreover, the type strains of the type species of Klebsiella and Raoultella, which were described as two different genera (Drancourt et al, 2001), share 98.0 % 16S rRNA gene sequence similarity.…”
mentioning
confidence: 99%